Limnological variables as a determinant of fish parasites abundance in the Esa-Odo reservoir, Esa-Odo Southwestern Nigeria. (30th January 2023) - Emmanuel, Obayemi Oluwadamilare; Komolafe, Olaniyi Olusola; Onana, Edith Ediseimokumoh
Abstract: This study investigated fish parasites in relation to limnological variables of the Esa-Odo reservoir since the quality of the aquatic environment might influence parasitic infestation in fish. The purpose of this study was to provide information on the parasite species of the reservoir due to their public health concern and their relationship with selected water quality parameters. The water quality and parasite examinations were analyzed based on standard protocols in the laboratory. The results showed that water quality parameters were not significantly different ( p > 0.05) across the zones. Seasonally, mean water temperature, pH, TDS, DO, organic matter, COD and turbidity were significantly different ( p < 0.05) across the different zones of the reservoir while electrical conductivity, alkalinity, NO3 -, and PO4 3- were not significantly different ( p > 0.05). Clinostomum tilapiae, Clinostomum sp., Euclinostomum heterostomum, Procamallanus laevionchus, and Lytocestus sp. were recovered in all the fish sampled. The overall prevalence of the fish parasites was 9.8% with an intensity of 2.13. The result indicated fish parasites had a strong positive correlation with certain water quality properties and parasite abundance which suggested that water quality could determine parasitic loads in fishes of the Esa-Odo reservoir. HIGHLIGHTS: The study provided the first record of an additional fish parasite in the Esa-Odo reservoir fish community. It also pinpoints the relationship between fish parasites and selected water quality. The selected limnological variables determine the abundance of fish parasites. This study will assist in further research of parasite vectors in the reservoir. It will encourage proper monitoring of the fisheries resources of the reservoir. Graphical Abstract